KINERJA PENGELOLAAN BELANJA PADA ANGGARAN PENDAPATAN DAN BELANJA DAERAH (APBD) KOTA PONTIANAK PADA ERA OTONOMI DAERAH TAHUN 2007 2011 - ME, ZAHRAWANI (Jurnal Ekonomi Daerah (JEDA), 2013)
ABSTRACT This study aims to analyze the performance of expenditure management and growth of the city government spending on regional autonomy. Each region in the implementation of regional autonomy, autonomy required to be able to run as well as possible and in demand to make changes, one change that should be run in the era of regional autonomy, namely changes in budget preparation. Budget and Expenditure (Budget) compiled with the performance approach. The method used in this research is descriptive method which is a method that aims to describe the study or description of something that is researched suitable for what happens on the field. Thought process in this study is prepared on the basis of empirical and deductive thinking. This research uses time series data (time series) for 5 years (2007 s / d 2011). Source of data used are secondary data. Results of this study indicate that the management of Pontianak City Government expenditure has been very good, in terms of spending growth over the 5-year budget from the year 2007 to 2011, the city of Pontianak always increase either the total expenditure budget planning and expenditure. Keywords : Expenditure Performance